2013
DOI: 10.5194/acp-13-3363-2013
|View full text |Cite
|
Sign up to set email alerts
|

Iodine monoxide in the Western Pacific marine boundary layer

Abstract: Abstract. A latitudinal cross-section and vertical profiles of iodine monoxide (IO) are reported from the marine boundary layer of the Western Pacific. The measurements were taken using Multi-Axis Differential Optical Absorption Spectroscopy (MAX-DOAS) during the TransBrom cruise of the German research vessel Sonne, which led from Tomakomai, Japan (42° N, 141° E) through the Western Pacific to Townsville, Australia (19° S, 146° E) in October 2009. In the marine boundary layer within the tropics (between 20° N … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(121 citation statements)
references
References 69 publications
8
108
4
1
Order By: Relevance
“…Additionally, the measured emission rates of iodinated VOCs are unable to explain the observed levels of IO and I 2 Jones et al, 2010b;Großmann et al, 2013;Lawler et al, 2014). Several mechanisms have been introduced to explain the observations and are still under active discussion (e.g.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…Additionally, the measured emission rates of iodinated VOCs are unable to explain the observed levels of IO and I 2 Jones et al, 2010b;Großmann et al, 2013;Lawler et al, 2014). Several mechanisms have been introduced to explain the observations and are still under active discussion (e.g.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…It is based on the measurement of sunlight scattered at multiple elevation angles towards the horizon, thus increasing the sensitivity to absorbers present close to the ground compared to the zenith viewing geometry (Hönninger et al, 2004). MAX-DOAS studies published so far have been mainly focused on the retrieval of NO 2 (e.g., Wittrock et al, 2004;Vlemmix et al, 2010;Frins et al, 2012;Hendrick et al, 2014;Ma et al, 2013;Wang et al, 2014), halogen oxides like BrO and IO (e.g., Frieß et al, 2011;Großmann et al, 2013), formaldehyde (e.g., Heckel et al, 2005;Wagner et al, 2011), and aerosols (e.g., Wagner et al, 2004;Frieß et al, 2006;Clémer et al, 2010). A lot of work has been done on MAX-DOAS measurements of volcanic SO 2 (e.g., Bobrowski et al, 2007;Galle et al, 2010), but so far only a few studies deal with MAX-DOAS observations of this species in polluted areas (e.g., Irie et al, 2011;Lee et al, 2008;Wu et al, 2013), despite the fact that, as for other trace gases like NO 2 , HCHO, and BrO, the combination of both surface concentration and VCD retrievals makes MAX-DOAS a useful technique for validating SO 2 satellite data.…”
Section: T Wang Et Al: Evaluation Of Tropospheric So 2 In Xianghementioning
confidence: 99%
“…Modelling studies have shown that these levels of IO cannot be sustained by the measured iodocarbon fluxes and that an additional source of reactive iodine from the open ocean, equivalent to > 50 % of the total surface iodine emission, is required to match the observations Mahajan et al, 2010). Correlation studies of ground-and ship-based IO and reactive iodine (IO x = IO + I) measurements with oceanic variables have shown that there is a negative correlation with Chl a and CDOM (colored dissolved organic matter), suggesting that the additional iodine production over the oceans is not biological and could be inhibited by the presence of increased biological activity or organic matter Gómez Martín et al, 2013;Großmann et al, 2013). This provides evidence for the widespread abiotic iodine source proposed by Garland and Curtis (1981): the sea surface oxidation of I − by O 3 to yield HOI and I 2 , which are then either released directly to the atmosphere or react with dissolved organic matter (Garland and Curtis, 1981;Martino et al, 2009;Carpenter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent ground-, ship-and aircraft-based measurements have found that IO is ubiquitous over the open oceans, with MBL-averaged mixing ratios of around 0.5 pptv, and surface mixing ratios of up to 3 pptv (Allan et al, 2000;Mahajan et al, 2010Mahajan et al, , 2012Dix et al, 2013;Gómez Martín et al, 2013;Großmann et al, 2013). Modelling studies have shown that these levels of IO cannot be sustained by the measured iodocarbon fluxes and that an additional source of reactive iodine from the open ocean, equivalent to > 50 % of the total surface iodine emission, is required to match the observations Mahajan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%